Application of Fermented Date Seeds for Copper Ion Removal from Wastewater: A Sustainable Adsorption Approach - Al-Saadi, Farah (Indonesian Journal Publisher, 2025)
This research investigates the feasibility of employing fermented date seeds (FDS) as an efficient and environmentally friendly adsorbent for removing copper ions (Cu2+) from wastewater. Date seeds, an abundant by-product in date-producing regions, can be managed sustainably by repurposing them as a heavy metal adsorbent from date vinegar production. The vinegar fermentation process partially activates the seeds, enhancing their adsorptive properties. The surface properties of the FDS were analyzed using techniques such as Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and SEM-EDX. The chemical oxygen demand (COD) test is used to evaluate the stability of organic matter in the adsorbent derived from FDS. Batch adsorption studies were conducted to determine the best conditions for Cu ion removal, including contact time, initial metal concentration, adsorbent dosage, and pH level. The FDS adsorption capacity is 4.76 mg g⁻¹, achieved within an equilibrium time of 90 minutes at pH 5 and 25 °C. The isotherm and kinetic models were applied to understand the adsorption mechanism, with results indicating a good fit for Freundlich isotherm and pseudo-second-order kinetics. In addition, the FDS shows effectiveness, with a COD value of 150 mgO2/L. Fermentation stabilizes organic components, reducing leaching risk and improving water treatment performance.